Um Estudo Empírico Exploratório em Confiabilidade de Sistemas Operacionais - Antunes, Marcela; Matias Jr., Rivalino (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
In this paper, we conduct an empirical exploratory study on OS reliability. We analyze more than 30,000 real OS failure data collected from different workplace environments. The results show that the main cause of OS failures is related to OS services. The Gamma and Weibull density functions presented the best fit to the OS failure data. OS kernel failures were more prevalent in enterprise workplaces than academics.